Does adjuvant treatment improve prognosis after curative resection of ampulla of Vater carcinoma? A multicenter retrospective study. (15th August 2020) - Kim, Hyung Sun; Jang, Jin‐Young; Yoon, Yoo‐Seok; Park, Sang‐Jae; Kwon, Wooil; Kim, Sun‐Whe; Han, Ho Seong; Han, Sung‐Sik; Park, Joon Seong; Yoon, Dong Sup
Abstract: Background/Purpose: Ampulla of Vater (AoV) carcinoma is a rare tumor that accounts for approximately 0.2% of gastrointestinal malignancies. There are no clinical guidelines concerning the treatment of AoV carcinoma. This study aimed to investigate the effectiveness of adjuvant treatment in AoV carcinoma following curative resection and define the "high‐risk" group. Methods: Clinical data of patients who underwent curative resection for AoV carcinoma in four hospitals, namely Yonsei Gangnam Severance Hospital, Seoul National University Hospital, Seoul National University Bundang Hospital, and National Cancer Center (n = 651; 2002–2015), were reviewed. Overall survival (OS) and recurrence‐free survival (RFS) rates were compared using Kaplan–Meier estimates. Results: Data of 651 patients who had undergone curative resection were retrospectively reviewed. Age, T stage, N stage, and differentiation type remained strong and independent risk factors for RFS and OS. In early‐stage AoV carcinoma (T1N0, T2N0), the non‐adjuvant group had better prognosis based on the RFS and OS than the adjuvant group ( P  < .001, P  = .007). In advanced T stage (T3N0, T4N0), the adjuvant group had better prognosis than the non‐adjuvant group, but the difference was not statistically significant ( P  > .05). In node‐positive patients (any T, N1/2), adjuvant treatment did not affect RFS and OS ( P  > .05). Conclusions: Adjuvant treatment after curative resection of AoV carcinoma is not associated with improved survival. The high‐risk group (node‐positive or advanced T stage (T3, T4)) treated with adjuvant treatment was not statistically associated with improved survival; however, our study showed that the adjuvant treatment for the high‐risk group might help achieve better patient outcome. Abstract : Highlight This multicenter study investigated the effectiveness of adjuvant treatment in ampulla of Vater carcinoma following curative resection. Although adjuvant treatment in high‐risk patients, defined as node‐positive or having advanced T stage, was not statistically associated with improved survival, Kim and colleagues concluded that it might help achieve better patient outcomes.